Resource efficiency complexity and the commons : the paracommons and paradoxes of natural resource losses, wastes and wastages - Lankford, Bruce A. (London : Earthscan from Routledge, 2013)
"The efficient use of natural resources is key to a sustainable economy, and yet the complexities of resource efficiency have not previously been studied in great depth. In this challenging book, the author proposes a major advance in our understanding of this topic by analysing resource efficiency from the perspective of common pool resources, particularly "the commons" of water resources and its use in irrigated agriculture. He proposes a novel concept of "the paracommons", through which the savings of increased resource efficiency can be viewed. By recycling, economising and avoiding losses, wastes and wastages, these saved resources are then available for further use by the same user, other competing stakeholders or return to the common pool resource. The paracommons is thus a commons of - and competition for - resources freed up by changes to the efficiency of natural resource systems. The idea can be applied to a wide range of resources such as water, energy, forests and high-seas fisheries. Five key issues are explored: the complexity of resource use efficiency; the uncertainty of efficiency interventions and outcomes; the destinations of and competition over freed up wastes and wastages; implications for conservation; and the interconnectedness of users and systems brought about by changes efficiency. The book shows how these ideas put efficiency on a par with other criteria and dimensions of resource governance and sustainability such as equity, justice, resilience, access and adequacy"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Waste minimization; Green technology; Electronic books